A Clinical Study to Evaluate the Therapeutic Effect of Drug Tagaradi Kwath in the Management of Anidra (Insomnia) – A Research Article - Singh, Sanjay; Sohgoura, Deepak; Patil, Umesh; Mishra, Ratnaprava (International Research Journal of Ayurveda & Yoga, 2022)
Anidra (Insomnia) is a type of sleep disorder in which individual feels difficulty in falling asleep, staying asleep or both. In Ayurveda, Anidra is indicated as Vata Nanatmaja Vikara by Acharya Charaka. Insomnia affects most of the people at any stage of life due to today’s stressful day to day life. Allopathic hypnotic drugs are used to treat insomnia in acute stage, but long-term use can lead to dependency and withdrawal symptoms along with other side effects. In present study a polyherbal compound Tagaradi kwath consist extracts of Tagara, Turagagandha, Parpati, Shankhpushpi, Tridasavitapi, Tikta, Bharti (brahmi), Bhutakesi, Jaladhara, Krtamala, Cetaki and Gostana is used to check its efficacy in the management of insomnia. Aim: A clinical study to evaluate the therapeutic effect of drug Tagaradi kwath in the management of Anidra (Insomnia). Materials and methods: Total 30 newly diagnosed patients of age group 15 to 70 years of insomnia who were not taking any other hypnotic medicine were selected and administered 50ml of Kwath at bedtime for 1 month. Assessment was done considering the overall improvement of sleep quality according to Athens Insomnia Rating Scale, improvement in associated complains, relieving of anxiety and depression. Observations: The information gathered on the basis of observations was subjected to statistical analysis. The Paired ‘t’ test was used to check the significance of objective criteria. Results: The results showed that the trial drug had Significant effect on almost all the mentioned parameters of Insomnia.